CERAI BERSYARAT (SHIGHAT TA’LIQ) MENURUT DUAL SISTEM HUKUM (Hukum Islam dan Hukum Perdata) - Nurhadi Nurhadi (Universitas Muhammadiyah Mataram, 2020)
Marriage is a sacred covenant that unites two deeply bound human beings (mitsaqan ghalizha). The agreement was concluded in a consent agreement between guardian and future husband. Indonesian civil law requires saying the husband's sighat ta'liq to his wife. The essence of sighat ta'liq is conditional divorce between the two. Using normative (doctrinal) legal research, and comparative law approach (fiqh of comparative Mazhab). The results of the study explain that Islamic law assesses a legal marriage if enough conditions and harmony, without sighat ta'liq. Indonesian sighat ta'liq requirements are in government policy through the decree of the minister of religion number 3 of 1953. The aim of the sighat ta'liq is to protect the wife from the abuse of her husband, if the husband violates, the wife has the right to sue in a religious court (divorce). Lafadz sighat ta'liq was made referring to the regulation of the minister of religion number 2 of 1990, but the lafadz contained an understanding of